Employee Coping Strategies in Dealing with Workplace Conflict - Dwi Dinarsih, Mustika; Pajarani Mogar Setyoningsih; M. Fa'iq Teza Putra; Lucia Rini Sugiarti; Fendy Suhariadi (Journal of Educational Management Research, 2025)
Work conflict is an inevitable reality in modern organizations, especially in the digital era full of pressure and structural dynamics. This study aims to explore employees' coping strategies in dealing with work conflict. Using a qualitative case study approach, data were obtained through in-depth interviews with three informants who were purposively selected based on their position, length of service, and conflict involvement. The results of thematic analysis revealed three main categories of coping strategies: problem-focused coping, emotion-focused coping, and avoidance-oriented coping. The choice of strategy is greatly influenced by individual perceptions of conflict, social support, and organizational culture. Appropriate coping strategies have been shown to play a role in maintaining psychological stability, increasing productivity, and preventing burnout. These findings contribute to the development of coping strategy theory in the context of work conflict and provide practical implications for HR management policies that are oriented towards employee psychological well-being.